Análisis de contenido de las publicaciones sobre clusters y distritos industriales en las revistas Espa\~nolas de economia - Josep Capó-Vicedo; Maria Teresa Martínez-Fernández; Teresa Vallet-Bellmunt; Manuel Expósito-Langa (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2011)
In recent decades, regional production patterns are the subject of scientific debate by researchers. However, there is a lack of previous literature review work. This gap advises us to perform a content analysis, choosing a sufficiently large temporal area, 1998 to 2008. We have selected the main Spanish scientific journals of Economics, obtaining a database composed by 98 contributions, in which we have studied the evolution of its scientific nature, research groups and/or universities, the research agenda and methodology. This will allow us to know the level of development of these areas and propose future research lines.
Keywords: R11; 330; territory; industrial district; cluster; regional development; content analysis